Referral letters in oral medicine: an approach for the general dental practitioner - Navarro, Cláudia Maria [UNESP]; Onofre, Mirian Aparecida [UNESP]; Sposto, M. R. (Churchill Livingstone, 2001)
The aim of this study was to analyze the contents of referral letters related to clinical history and reason for consultation. A total of 236 consecutive referral letters were evaluated. Analysis of the referral letters was based on key items concerning patient identification. chief complaint, previous consultation. laboratory investigation and use of drugs for the chief complaint. A database was organized (Epinfo 6.04) and the chi (2) test (a = 0.05) was applied to the results. of the 800 files examined. only 30%, (236) had a referral letter. of the 236 referral letters. 67% were from dentists, 22% from physicians and 11% from unidentified professionals. Patient age did not appear in 70%, of the letters and the chief complaint was mentioned only in 55%. The letters had no details such as description of the oral lesion (80%), anatomical site (34%), size (99%), symptoms (83%), or period of evolution (92%). Clinical diagnosis was not included in 84% of the letters. Less than 5% of the referral letters contained information about previous consultation and laboratory investigation. The chi (2) test showed significant differences for ail items of the referral letter. Referral letters did not satisfy minimal requirements about clinical history or reason for consultation. leading to failed communication among professionals. Based on this study, we suggest that standard letters are important to improve the quality of the letters, reducing the rate of omission of relevant items.
Keywords: referral letters; dentist; oral medicine; consultation